Implementasi RUBECO dalam Pembelajaran Daring Guna Membangun Pemahaman TPACK Guru di SD Muhammadiyah Kleco - Purwanti Purwanti; Lisa Retnasari; Hendra Hermawan (Universitas Tidar, 2022)
Teachers as a source of learning for students must be able to improve education through the times by applying information and communication technology in education. This study aims to find out how the implementation of RUBECO in online learning is to build an understanding of teacher TPACK at SD Muhammadiyah Kleco and the supporting and inhibiting factors. This research was conducted with a qualitative descriptive research method. This qualitative descriptive study describes the research data that has been obtained. Data collection techniques used in the form of interviews, observation, and documentation. The teacher understands the learning technology in the form of the RUBECO application, uses the RUBECO application as an online learning medium, and understands the function of the RUBECO application for online learning. Teachers have an understanding of all components of TPACK, namely and the importance of TPACK for online learning so that the implementation of RUBECO is able to build teacher understanding of TPACK. Teachers understanding of TPACK has been seen in online learning using the RUBECO application. The implementation of RUBECO is supported by several factors so that it can be carried out properly and smoothly. Several inhibiting factors were also encountered in the implementation of RUBECO but they could be overcome and these inhibiting factors were not significant obstacles. This TPACK capability contributes so that teachers continue to develop TPACK abilities in learning and create quality learning.